The medical internship from a human rights-based approach to health. The cases of Costa Rica and Mexico (Revista Electrónica Calidad en la Educación Superior, 2023)
This study investigates, from a human rights-based approach to health, the training process of medical students in the last year of their career or internship.  This is a descriptive, cross-sectional study in a public Mexican university and a private Costa Rican university, with a population of 532 interns, an anonymous, voluntary survey of 33 items [Cronbach's alpha=0.926].  In both countries, there is a lack of counseling and supervision by teachers, as well as working hours in excess of 80 hours per week.  Costa Rica and Mexico share problems of medical education during internship and have common challenges regarding the promotion of the right to education in medical units.
Keywords: Medical education; Medical internship; Education rights; Right to health; Patient safety